Pregunta
upstudy study bank question image url

The function \( f \) is given by \( f(x)=4 \cdot 3^{(z-2)}+1 \). The function \( g \) is given by \( g(x)=f^{-1}(x) \). For which of the following values does \( g(x)=-3 x \) ?

Ask by Rodriquez Lyons. in the United States
Jan 30,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

To find the values of \( x \) where \( g(x) = -3x \), first find the inverse function \( g(x) = f^{-1}(x) \) of \( f(x) = 4 \cdot 3^{(x-2)} + 1 \). Setting \( g(x) = -3x \) leads to a complex equation that may require numerical methods to solve. After testing integer values, no exact solutions are found within the tested range.

Solución

To find the values for which \( g(x) = -3x \), we first need to determine the inverse function \( g(x) = f^{-1}(x) \) of the function \( f(x) = 4 \cdot 3^{(x-2)} + 1 \). ### Step 1: Find the inverse function \( f^{-1}(x) \) 1. Start with the equation for \( f(x) \): \[ y = 4 \cdot 3^{(x-2)} + 1 \] 2. Rearrange the equation to solve for \( x \): \[ y - 1 = 4 \cdot 3^{(x-2)} \] \[ \frac{y - 1}{4} = 3^{(x-2)} \] 3. Take the logarithm of both sides: \[ \log_3\left(\frac{y - 1}{4}\right) = x - 2 \] 4. Solve for \( x \): \[ x = \log_3\left(\frac{y - 1}{4}\right) + 2 \] Thus, the inverse function is: \[ f^{-1}(x) = \log_3\left(\frac{x - 1}{4}\right) + 2 \] ### Step 2: Set up the equation \( g(x) = -3x \) Now we set \( g(x) = f^{-1}(x) \) equal to \( -3x \): \[ \log_3\left(\frac{x - 1}{4}\right) + 2 = -3x \] ### Step 3: Solve the equation 1. Rearranging gives: \[ \log_3\left(\frac{x - 1}{4}\right) = -3x - 2 \] 2. Exponentiating both sides to eliminate the logarithm: \[ \frac{x - 1}{4} = 3^{-3x - 2} \] 3. Multiply both sides by 4: \[ x - 1 = 4 \cdot 3^{-3x - 2} \] \[ x - 1 = \frac{4}{9} \cdot 3^{-3x} \] 4. Rearranging gives: \[ x - 1 = \frac{4}{9} \cdot \frac{1}{3^{3x}} \] ### Step 4: Solve for \( x \) This equation is complex and may require numerical methods or graphing to find solutions. However, we can also check specific values of \( x \) to see if they satisfy the equation. Let's check some integer values for \( x \): - For \( x = 0 \): \[ 0 - 1 = -1 \quad \text{and} \quad \frac{4}{9} \cdot 3^{0} = \frac{4}{9} \quad \text{(not equal)} \] - For \( x = 1 \): \[ 1 - 1 = 0 \quad \text{and} \quad \frac{4}{9} \cdot 3^{-3} = \frac{4}{9} \cdot \frac{1}{27} = \frac{4}{243} \quad \text{(not equal)} \] - For \( x = -1 \): \[ -1 - 1 = -2 \quad \text{and} \quad \frac{4}{9} \cdot 3^{3} = \frac{4}{9} \cdot 27 = 12 \quad \text{(not equal)} \] - For \( x = -2 \): \[ -2 - 1 = -3 \quad \text{and} \quad \frac{4}{9} \cdot 3^{6} = \frac{4}{9} \cdot 729 = 324 \quad \text{(not equal)} \] Continuing this process or using numerical methods will yield the specific values of \( x \) for which \( g(x) = -3x \). ### Conclusion To find the exact values, numerical methods or graphing tools may be necessary. Would you like me to perform a numerical solution for this equation?

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve for the values of \( x \) where \( g(x) = -3x \) given the function \( f(x) = 4 \cdot 3^{(x-2)} + 1 \), we first need to find the inverse function \( g(x) = f^{-1}(x) \). 1. Set \( y = f(x) \): \[ y = 4 \cdot 3^{(x-2)} + 1 \] Rearranging gives: \[ y - 1 = 4 \cdot 3^{(x-2)} \] Dividing both sides by 4: \[ \frac{y - 1}{4} = 3^{(x-2)} \] Taking the logarithm base 3 on both sides: \[ x - 2 = \log_3\left(\frac{y - 1}{4}\right) \] Thus, we obtain: \[ x = 2 + \log_3\left(\frac{y - 1}{4}\right) \] So, the inverse function is: \[ g(y) = 2 + \log_3\left(\frac{y - 1}{4}\right) \] 2. Next, we need to set this equal to \( -3x \): \[ 2 + \log_3\left(\frac{x - 1}{4}\right) = -3x \] 3. Solve for \( x \): \[ \log_3\left(\frac{x - 1}{4}\right) = -3x - 2 \] Exponentiating both sides with base 3 gives: \[ \frac{x - 1}{4} = 3^{-3x - 2} \] Therefore, \[ x - 1 = 4 \cdot 3^{-3x - 2} \] \[ x = 4 \cdot 3^{-3x - 2} + 1 \] While the equation is complex to solve algebraically, we can approach values to find solutions numerically or graphically. 4. By testing values: - For \( x = 0 \): \[ g(0) = f^{-1}(0) \text{ does not exist since } f(x) = 1 \text{ for all } x. \] - For \( x = -1 \): \[ -3(-1) = 3; \text{ check if } g(3) = 3. \] - Continue testing further values until you find points of intersection. This leads to finding specific values where the condition holds. Therefore, \( g(x) = -3x \) can be solved for values in the set \( x \) based on calculations or rooting towards equations generated via numerical estimation. Upon deeper exploration, typically using graphing or numerical tools (e.g., plotting both functions or utilizing numerical solvers), we can identify specific intersections leading to properties of the inverse function at respective coordinates. Thus, the solution set can be found through exploration within the bounds of possible values or estimated numerical values.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad